2021
DOI: 10.21037/atm-20-6180
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict survival in patients with acute-on-chronic hepatitis B liver failure after liver transplantation

Abstract: Background: Individualized prediction of survival after liver transplantation (LT) for patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) has not been well investigated. This study aimed to develop a prognostic nomogram for patients with HBV-ACLF undergoing LT. Methods: The nomogram was derived from a retrospective study of 290 patients who underwent LT for HBV-ACLF at the Third Affiliated Hospital of Sun Yat-sen University between January 2012 and December 2017. Concordance inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several previous studies have evaluated factors associated with prognosis of HBV-ACLF patients following LT. For example, a study of 290 patients with ACLF after LT found that recipient WBC count, the ratio of alanine aminotransferase (ALT) to aspartate aminotransferase (AST), and the number of organs that failed were prognostic of survival [ 13 ]. Another study, of 78 patients, reported that patients with initial COSSH-ACLF grade 3 and with grades 2 and 3 on days 3–7 after diagnosis had poorer prognosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have evaluated factors associated with prognosis of HBV-ACLF patients following LT. For example, a study of 290 patients with ACLF after LT found that recipient WBC count, the ratio of alanine aminotransferase (ALT) to aspartate aminotransferase (AST), and the number of organs that failed were prognostic of survival [ 13 ]. Another study, of 78 patients, reported that patients with initial COSSH-ACLF grade 3 and with grades 2 and 3 on days 3–7 after diagnosis had poorer prognosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, liver transplantation (LT) is the most effective treatment for patients with HBV-ACLF [ 8 12 ]. Although factors prognostic of LT in patients with ACLF have been widely reported, few studies to date have focused on HBV-related ACLF and assessed the post-LT prognosis of patients with HBV-ACLF; moreover, those studies included relatively small numbers of patients and did not completely evaluate indicators [ 12 , 13 ]. No studies to date have reported reliable and uniform prognostic factors that can predict survival outcomes in LT recipients who developed HBV-ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…Acute-on-chronic liver failure (ACLF) is a severe clinical syndrome characterized by acute liver decompensation, organ failures, and a high rate of short-term mortality triggered by an acute insult. [1][2][3] In China, HBV-ACLF accounts for more than 70% of ACLF cases due to the high prevalence of HBV infection. 4,5 While liver transplantation (LT) is the definitive therapeutic option for liver failure, 6 the shortage of LT resources in China leads to an extremely poor prognosis for HBV-ACLF patients, with a high short-term mortality rate ranging from 29.7% to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a more finely-tuned approach for predicting personalized liver fibrosis and inflammatory responses of chronic HBV-infected patients is necessary. In recent years, nomograms have been emphasized in the prediction of HBV-related diseases, such as, in predicting survival in patients with acute-on-chronic HBV liver failure after liver transplantation ( 13 ), in assessing mortality in patients with acute and chronic HBV liver failure ( 14 ).…”
Section: Introductionmentioning
confidence: 99%